THE PROBLEM OF ENSURING THE SECURITY OF PROFESSIONAL RADIO COMMUNICATION SYSTEMS IN CRITICAL INFRASTRUCTURES - Shavlovsky, Yaroslav; Perederii, Serhii; Bychkov, Volodymyr (Ukrainian Information Security Research Journal, 2024)
This paper reviews the existing and expected scenarios of unauthorized impacts on communication systems in critical information structures. It has been established that the area of increased risk of such impacts is focused on the interfaces between external devices and the SoC chip. Examples are given of grouping a large number of sub-scriber terminals operating under a single program of unauthorized influences, and the level of penetration can be increased many times over. It is noted that such possibilities become more realistic with the introduction of 5G generation systems that provide for M2M operation. The purpose of this review is to determine an approach to modeling the processes of protecting information from leakage through radio channels of communication systems and to develop engineering and technical measures for the design and implementation of appropriate information security systems.